2021
DOI: 10.1007/s11948-021-00307-8
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Theory of Digital Well-Being: Reimagining Online Life After Lockdown

Abstract: Global lockdowns during the COVID-19 pandemic have offered many people first-hand experience of how their daily online activities threaten their digital well-being. This article begins by critically evaluating the current approaches to digital well-being offered by ethicists of technology, NGOs, and social media corporations. My aim is to explain why digital well-being needs to be reimagined within a new conceptual paradigm. After this, I lay the foundations for such an alternative approach, one that shows how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Contemporary conceptualizations of SWB should include digital and cultural aspects of well‐being given the paradigm shift towards virtual mediums, accelerated by COVID‐19. Finding the right balance, by being able to focus time with technology and minimizing distractions, will determine digital well‐being of students, and overall well‐being of consumers of higher education services (Dennis, 2021). Digital well‐being is also crucial for digital agility in today's environment (Öste, 2020).…”
Section: Where Should We Be Heading?mentioning
confidence: 99%
“…Contemporary conceptualizations of SWB should include digital and cultural aspects of well‐being given the paradigm shift towards virtual mediums, accelerated by COVID‐19. Finding the right balance, by being able to focus time with technology and minimizing distractions, will determine digital well‐being of students, and overall well‐being of consumers of higher education services (Dennis, 2021). Digital well‐being is also crucial for digital agility in today's environment (Öste, 2020).…”
Section: Where Should We Be Heading?mentioning
confidence: 99%
“…Where it is suggested to have three important dimensions: Holistic digital practices of an individual, harnessing the harms or benefits of those digital practices, and the effects of those harms and benefits on individual well-being (Gui & Büchi, 2021) [13] . Researchers have further suggested that the ability to maintain digital well-being is generally dependent upon the individual's self-regulation of their digital device usage (Burr et al, 2020;Dennis, 2021) [4,7] . Wherein, it's an individual's responsibility to unplug from digital devices, regulate digital device usage, and practice self-control for attaining digital well-being (Thomas et al, 2022) [31] .…”
Section: Review Of Literaturementioning
confidence: 99%
“…Various organizations and researchers have suggested the need to understand the concept of digital well-being in the ambit of the contemporary increase in digital device usage. Where the organizations like Google introduced its "Digital Well-being" initiative in 2018 (Google, 2018) [11] , highlighting the need to find a balance with the technology usage and regulating the digital distractions (Dennis, 2021; Google, 2018) [7,11] . Researchers have viewed the radical concept of digital well-being from various angles.…”
Section: Introductionmentioning
confidence: 99%
“…Most often, these are components such as a digital educational environment, digital educational space, digital technologies, politics in digital learning, digital ethics, etcetera. (Bertram, 2020;Burr et al, 2019;Dennis, 2021;Lindberg, 2020;Pachero et al, 2020). Of particular interest among researchers is the study of such a component of digital pedagogy as a result (Chernyshov, 2021;Nazarov et al, 2021).…”
mentioning
confidence: 99%